STUDI LITERATUR: ANALISIS HUBUNGAN DAN PENGARUH LINGKUNGAN BELAJAR TERHADAP MOTIVASI BELAJAR, RESILIENSI MATEMATIS, DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Alvi Hidayatusholihah; Taufik Muhtarom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship and influence of the learning environment on learning motivation, mathematical resilience, and mathematics learning outcomes of elementary school students. This research method uses a literature study method by reviewing 43 relevant journal articles published between 2020-2025. Data collection techniques are carried out through the Google Scholar database using specific keywords. The article selection process is carried out through the process stages, include, exclude. Includes: (1) researchers enter the keyword